The Effect of Receiver Tube Design with a Tube Length of 85 mm on COP and Electrical Power Consumption in Air Conditioning Units for Ship Accommodation Spaces - Urip Prayogi; Dwisetiono; Arif Winarno; Sutrisno; Rasional Sitepu (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2026)
The high temperature on ships reduces crew comfort, making air conditioning essential to maintain a suitable environment. To optimize cooling and minimize energy use, this study examines the design and construction of a receiver tube aimed at reducing the compressor workload of the ship’s air conditioning (AC) system. The research employs an experimental method, testing the AC performance before and after installing a receiver tube. Parameters observed include the Coefficient of Performance (COP), electric power consumption, and electricity costs. Results show that the receiver tube with an 85 mm length variation produced the best performance. During a 60-minute test, it achieved the highest COP value of 30.8 and the lowest electric power consumption of 242 watts. Based on electricity cost calculations, the 85 mm receiver tube requires IDR 251,700 for one month of continuous operation (24 hours daily). When applied to the OKI 004 ship, the use of this receiver tube reduces AC operational costs by IDR 549,240 per month. These findings demonstrate that the receiver tube not only maintains effective cooling performance but also significantly lowers energy consumption and operating expenses. The implementation of this design contributes to efficiency in ship accommodation cooling systems, providing both economic and practical benefits for maritime operations.